Orb-weaving spider diversity in the Iberá Marshlands, Argentina - Rubio, Gonzalo Daniel (2010)
The Iberá Marshlands RAMSAR reserve, in the northeast of Argentina, is one of the largest and most important wetlands of America. In this study we assess orb-weaving spider (Araneae: Orbiculariae) diversity in this reserve, analyzing different facets of local diversity (species richness, diversity, evenness and taxonomic distinctness), and the contribution of species differentiation (beta diversity) among localities and habitat types to the composition of regional diversity. We found 1657 individuals of 59 orb-weaving spider species/morphospecies. Local diversity differs among the three sampled localities. At the habitat level, the different facets of biodiversity followed a clear pattern, where woodlands have higher species richness, diversity, evenness and taxonomic distinctness than savannas. Savanna sites shared a common spider species composition, while woodland communities have high values of complementarity. Thus, beta diversity has a very high contribution to the regional diversity of the orb-weaving spiders in the Iberá Marshlands. We suggest that conservation management in the reserve should be directed towards promoting natural spatial heterogeneity, giving special protection to habitat mosaics in different localities.